IMPLEMENTASI PENGELOLAAN MAKANAN HALAL DI INDONESIA (Studi Analisis UU Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal) - Abd. Rohman Fahruddin (Universitas Muhammadiyah Jember, 2019)
Today the concept of halal has become a trend in the development of islamic economics in Indonesia, starting from the emergence of halal product, halal cosmetics, halal fashion and halal tourism to lifestyle. Halal concept in various economic fields have not only become a trend in Indonesia but have expanded to foreign countries which in fact are not Muslim-majority countries such as Japan, Australia, Thailand, and New Zealand. Halal is a universal indicator for guaranteeing product quality and living standards (Gillani, Ijaz, Khan, 2016). Halal products and services are chosen by Muslims as a form of obedience to Islamic sharia law. Even thougt halal is very related to Muslims, it does not mean that consumers of halal products only come from Muslims. In the law of the Republic of Indonesia number 33 of 2014 concerning guarantee of halal products in article 3 states that all product that enter, circulate an trade in the territory of Indonesia must be halal certified. This study aims to explain the implementation of halal food management in Indonesia by using qualitative methods and by reviewing research result and developing report.